Homo Islamicus, Israf Control, And Impulse Buying: Financial Planning Mediation Among Muslim Paylater Users - Indah Rahmatillah; Maksum (Universitas Islam Darul 'ulum Lamongan, 2026)
The expansion of Pay Later services has significantly increased the ease of consumption while simultaneously encouraging impulse buying behavior, particularly among Muslim consumers. This phenomenon reflects a discrepancy between contemporary consumption practices and Islamic economic values. This study aims to analyze the influence of homo islamicus understanding and israf control on impulse buying behavior, with financial planning acting as a mediating variable. This research adopts a quantitative approach using survey data collected from Muslim Pay Later users. The data were analyzed using mediation analysis techniques. The results reveal that israf control has a significant direct effect on impulse buying, while homo islamicus understanding does not directly influence impulse buying. However, both variables indirectly affect impulse buying through financial planning as a mediating variable.. These findings indicate that a stronger internalization of Islamic values, combined with effective financial management, can reduce impulsive and uncontrolled consumption behavior. This study emphasizes the importance of integrating Islamic ethical principles with financial literacy to encourage more responsible consumption behavior in the digital era.